Pelatihan Pembuatan Web Dengan PHP Dan WordPress Pada SMA Negeri 4 Pangkalpinang - Agus Dendi Rachmatsyah; Burham Isnanto; Seno Hadi Saputro; Ellya Helmud; Ari Amir Alkodri (Jurnal Pengabdian Masyarakat Berbasis Teknologi, 2021)
The development of Science and Technology is getting faster and faster, especially in the field of Information Technology, one of which is website technology. Training on creating websites with php and WordPress was carried out at SMA Negeri 4 Pangkalpinang because the SMP Negeri was deemed not optimal in using existing information technology, therefore this service was carried out. The participants in this service were students of SMA Negeri 4 Pangkalpinang. In this service activity is to provide training and assistance in creating a website using PHP and WordPresss to students at SMA Negeri 4 Pangkalpinang. As for the benefits of this training, it is hoped that it can improve the ability of SMA Negeri 4 Pangkalpinang students in creating a database with Xampp as a server. The importance of this training for SMA Negeri 4 Pangkalpinang is because by looking at the times regarding sophisticated technology, students of SMA Negeri 4 Pangkalpinang are also required to be able to use this technology so as not to be left behind and gain new insights in the use of information technology.